Orthopaedic imaging : a practical approach - Greenspan, Adam.; Beltran, Javier (Philadelphia : Wolters Kluwer, 2021)
A trusted radiology reference in its 7th edition that's established as an ideal comprehensive source for guidance for both radiologists and orthopedic surgeons on musculoskeletal imaging. It will retain its large trim size as is well regarded for the large images and very telegraphic style of the content. Curated by renowned musculoskeletal authorities over 3500 images that encompass conventional radiography, ultrasound, CT, dualenergy, CT, PET-CT and all other diagnostic imaging modalities used to evaluate musculoskeletal disorders, including numbers examples of 3-D imaging. And guidance provided on choosing the best imaging approach for each patient--
Includes bibliographical references and index.
Keywords: Bone and Bones; Bone Diseases; Diagnostic Imaging